Essential oils as potential anti-staphylococcal agents - Piotr Szweda (Sciendo, 2018)
Antibiotic therapy of staphylococcal mastitis is characterized by significantly lower cure rates compared to infections caused by other microorganisms. Thus, it is necessary to search for new, alternative, non-antibiotic agents that are effective in the eradication of these bacteria. The aim of our research was to investigate the antimicrobial, especially anti-staphylococcal potential of a large collection (n=36) of essential oils (EOs). Investigation of the antimicrobial activity of tested oils was determined by using a serial, twofold dilution method in 96-wells microtiter plates under conditions recommended by the Clinical and Laboratory Standards Institute (CLSI). The preliminary analysis revealed that six oils, namely: Manuka, Thyme, Geranium, Cedar, Cinnamon (from bark) and Patchouli exhibited the highest activity against reference strains of bacteria. Significant anti-staphylococcal potential of these oils has been also confirmed for a group of 18 Staphylococcus aureus, 8 Staphylococcus epidermidis and 5 Staphylococcus xylosus strains isolated from cases of bovine mastitis. Especially high activity was observed for Cedar, Patchouli, Thyme and Manuka oils. The MIC (Minimal Inhibitory Concentration) values for Patchouli oil were in the concentrations range of 0.01 to 0.313% (v/v). The three other oils inhibited the growth of staphylococci isolated from mastitis in the concentrations range of 0.01 to 0.625% (v/v). Oils isolated from Cinnamomum cassia and Pelargonium graveolens revealed a bit lower, but still satisfactory activity (MIC values in the concentrations range of 0.02 to 1.25% (v/v) and from 0.078 to 1.25% (v/v), respectively). In many cases a slightly higher concentration of oils was required to obtain the bactericidal effect in comparison to growth inhibition. The time – kill kinetic assay revealed that the bactericidal effect was achieved after two hours incubation of the reference strain S. aureus PCM 2051 cells with Thyme oil at concentration equal to 2xMIC (1.25% (v/v)) or MIC (0.625% (v/v)). A slightly lower activity was observed in the case of Cinnamon oil, the bactericidal effect was achieved after 8 hours of incubation. The results of our research clearly indicate that some essential oils exhibit a promising antimicrobial activity and can be considered as alternative antistaphylococcal agents.